QR Code and its Security Issues - Shah, Dhwanish; Shah, Yash (International Journal of Computer Sciences and Engineering, 2014)
With the wireless media becoming the most accessible commodity of the time to the people, barcodes are used as the message carriers with significant information transferred through at both ends. This paper aims to provide details about the most commonly 2D barcode, QR code in respect to its structure, symbology. Also it gives overview of different schemes that the attacker can use to deceive the people by directing them to malicious websites almost similar in domain name to the source.